Explorations Gone Viral: A Comparative Study of Emergency Laparotomies in COVID-19 Positive vs COVID-19 Negative Patients at A Tertiary Care Hospital during the COVID-19 Pandemic - Dutt, Aishwarya; Bhandarwar, Ajay; Bakhshi, Girish; Dhimole, Nikhil; Padekar, Harshal; Dandge, Snehal; Lahoti, Kaushal; Chetan, Advaith; Raichur, Apoorva (Archives of Clinical and Biomedical Research, 2023)
Aim: To compare the mortality in emergency laparotomy cases between those with COVID-19 infection to those without the infection and to identify predicting factors that would help in optimum management for the same. Method: A prospective observational study was conducted in a tertiary care centre in Mumbai. Patients underwent exploratory laparotomy of which 20 were COVID-19 positive (Group A) while 20 were COVID-19 negative (Group B). Patient’s details with blood investigations, radiological investigations, preoperative and postoperative stay were taken into consideration. All these parameters were studied and compared in detail. Result: 40 cases that underwent emergency laparotomy for various causes were compared. Pulmonary complications were seen postoperatively in 45% patients of Group A and 15% patients of Group B. Mortality was seen in 40% cases of Group A of which 87.5% cases were due to postoperative respiratory complications due to COVID-19 infection. Group B had one mortality, due to septic shock. Mortality was significantly higher in Group A(p-value: 0.008). Comorbidities such as hypertension, diabetes mellitus and ischemic heart disease were seen to be associated with a higher incidence of mortality. Mortality was witnessed more in the age group above 40 years. High APACHE-II score and Computed Tomography severity index (CTSI) showed higher mortality. Antivirals did not show any effect on postoperative survival. Conclusion: Emergency operations can be taken up in COVID-19 positive patients with adequate precautions. Postoperative complications are related to comorbidities, age and CTSI. High index of suspicion for pulmonary complications and aggressive postoperative management with steroids gives improved outcomes.